The Resistance to The Objectification of Body in Emily Ratajkowski’s Memoir My Body - Muhammad Hafidz Hakami; Ruminda Ruminda; Agry Pramita (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research aims to contribute to the analysis of feminism and patriarchal culture related to the objectification of women's bodies and their resistance in the memoir My Body released in 2021 and written by Emily Ratajkowski. The memoir My Body (2021) illustrates that patriarchal culture grows and develops in people's lives as shown by the dominance of men over women in various aspects of life which causes women's bodies to be objectified so that they experience limited access in various fields of life. The analysis in this study includes the depiction of patriarchal culture and objectification of women's bodies in the memoir My Body (2021) and the resistance to patriarchal culture carried out by female characters in the memoir My Body (2021). In conducting the analysis, the researcher used the literary criticism method by using the theory of feminism from Helene Cixous' thoughts to analyse feminism related to the culture of objectification of women's bodies and their resistance. The results of this study found 4 data in the form of narratives. This research describes body objectification as a culture that limits women that makes women disadvantaged, the culture depicts women as figures who depend on male superiority, and as objects of male lust. In their resistance, women reject norms by writing. Women also resist the culture of objectification by being independent from male roles, independent in defending themselves, and independent in making life decisions. Women are also portrayed as rebelling against male control. This research makes an answer to Helene Cixous' theory of "why women should write" because they have to "fight" the norms and culture that limit and harm women themselves and only fellow women understand how to be in that position.